Enhancing the high-spin reactivity in C–H bond activation by Iron (IV)-Oxo species: insights from paclitaxel hydroxylation by CYP2C8 - Yue, Dongxiao; Hirao, Hajime (Frontiers in Chemistry, 2024)
Previous theoretical studies have revealed that high-spin states possess flatter potential energy surfaces than low-spin states in reactions involving iron(IV)-oxo species of cytochrome P450 enzymes (P450s), nonheme enzymes, or biomimetic complexes. Therefore, actively utilizing highspin states to enhance challenging chemical transformations, such as C-H bond activation, represents an intriguing research avenue. However, the inherent instability of high-spin states relative to lowspin states in pre-reaction complexes often hinders their accessibility around the transition state, especially in heme systems with strong ligand fields. Counterintuitively, our investigation of the metabolic hydroxylation of paclitaxel by human CYP2C8 using a hybrid quantum mechanics and molecular mechanics (QM/MM) approach showed that the high-spin sextet state exhibits unusually stability, when the reaction follows a secondary reaction pathway leading to 6β-hydroxypaclitaxel.We thoroughly analyzed the factors contributing to the enhanced stabilization of the high-spin state, and the knowledge obtained could be instrumental in designing competent biomimetic catalysts and biocatalysts for C-H bond activation.